Case Report: a newly described form of fixed subaortic stenosis in a feline patient - Cerbu, Maria; Constantin, Irina; Scurtu, Iuliu-Călin; Cerbu, Constantin; Tăbăran, Alexandru-Flaviu (Frontiers in Veterinary Science, 2025)
Fixed subaortic stenosis as a congenital heart defect has been reported in a relatively small number of cases. The classic description of feline subaortic stenosis reflects the presence of a fibrous ring just underneath the aortic valve. The present case has a unique morphological aspect, analogous with a rare human stenosis. A 15-month-old, ESH female presented with an anamnesis consisting of respiratory distress, apathy, and anorexia. The clinical examination displayed a patient with lethargy and severe dyspnea, whilst lung auscultation identified generalized bilateral pulmonary crackles. A systolic IV/VI parasternal murmur was identified on the left thorax, while the murmur intensity on the right side was III/VI. Electrocardiogram showed a sinus rhythm interrupted by ventricular ectopic beats. Two-dimensional (2D) echocardiography revealed a concentric hypertrophy of the left ventricle, with severe left atrium enlargement and mild pleural and pericardial effusion. A subaortic, hyperechoic structure was seen from the right parasternal five-chamber view, accompanied by post-stenotic aortic dilatation. The aortic peak velocity was 5.2 m/s, a feature that characterizes the severe form of aortic stenosis. The cat died shortly after presentation and necropsy was performed. Subaortic stenosis was confirmed on gross examination. The structure that induced stenosis of the left ventricle outflow tract (LVOT) had the appearance of a rudimental valve with moderator bands attached. Microscopically, it contains fibrous and smooth muscular tissue and cardiac conduction fibers. This type of subaortic stenosis resembles the cushion-like pseudovalve type described only in human cardiology. This is the first case describing clinical signs, ECG, echocardiography, and histopathological findings in a cat with cushion-like pseudovalve subaortic stenosis. Fixed subaortic stenosis is a rare congenital disease in cats, which should be taken into consideration in young cats with dyspnea and left ventricular hypertrophy.